Statins for primary prevention of cardiovascular disease and the risk of acute kidney injury. Issue 12 (13th September 2019) - Coste, Joël; Karras, Alexandre; Rudnichi, Annie; Dray‐Spira, Rosemary; Pouchot, Jacques; Giral, Philippe; Zureik, Mahmoud
Abstract: Purpose: To investigate the risk of acute kidney injury (AKI) in subjects initiating statin therapy for primary prevention of cardiovascular disease (CVD). Methods: A nationwide cohort study using French hospital discharge and claims databases was performed, studying subjects from the general population aged 40 to 75 years in 2009, with no history of CVD and no lipid‐lowering drugs during the preceding 3‐year period, followed for up to 7 years. Exposure to statins (type, dose, and time since first use) and to other drugs for CVD risk was assessed. The primary outcome was hospital admission for AKI. Results: The cohort included 8 236 279 subjects, 818 432 of whom initiated a statin for primary prevention. During 598 487 785 person‐months exposed to statins, 700 events were observed, corresponding to an incidence of AKI of 4.59 per 10 000 person‐years (7.01 in men, 3.01 in women). AKI mainly occurred in the context of organ failure, sepsis, and genitourinary disease. A 19% increased rate of AKI (hazard ratio = 1.19, 95%CI: 1.08‐1.31) was observed in men exposed to statins, whereas no increase in the overall risk of AKI was observed in women. However, exposure to high‐potency statins was associated with a 72% to 116% increased risk in both genders and a dose‐effect relationship observed for rosuvastatin and atorvastatin. No temporal pattern of occurrence nor interaction with drugs for CVD risk was observed. Conclusions: Although the overall risk of AKI appears moderately increased, more attention should be paid to renal function in subjects taking statins for primary prevention both in clinical practice and from a research viewpoint.